Search for tritium in air in a room equipped with 14 MeV neutron generator with tritiated targets. (June 2020) - Miecznik, M.; Mietelski, J.W.; Wójcik-Gargula, A.; Brudecki, K.; Dankowski, J.
Abstract: Eight documented tritiated targets were stored, as well as some very old targets with unknown activity, in a room equipped with an ING-114 14 MeV fast neutron generator. When the neutron generator was running, the tritiated targets were irradiated with a deuterium beam. The aim of this work is to determine the tritium content in the room's atmosphere, as well as the radiation exposure of workers in the room. In this study, isotopic exchange was assumed. This means that tritium from the targets diffused into the air, where it reacted immediately with oxygen particles to form vapour. These vapour molecules diffused into open vessels containing deionized water (50 ml in 120 ml plastic containers). Fifty vessels were arranged along the length (every 0.50 m) and width (every 1 m) of the room. Additionally, there were three vessels placed in the room for shorter periods (5, 7, and 12 days) together with a vessel that was exposed to the tritium for the full duration of the experiment (18 days) to determine the saturation curve. Based on the measured tritium contents, a map of the spatial distribution of tritium in the room was created. The results were used to calculate the radiation dose for a person working in the room and showed no significant contribution to the approved average annual dose for workers. Highlights: Determination of tritium activity concentration in air using isotopic exchange method. A map of the spatial distribution of tritium in the room. Determination of effective doses for workers based on activity concentration in the air.